APLES – The Achondroplasia Personal Life Experience Scale – Development of a Questionnaire to Assess Quality of Life, Burden of Disease and Functionality of Children with Achondroplasia - Janika Blömeke (2016)
Background: Achondroplasia is the most common form of disproportionate short stature. It is a result of an autosomal dominant mutation in the fibroblast growth factor receptor 3 gene (FGFR3), which causes an abnormality of cartilage and bone formation. Little is known about the health-related quality of life (HrQoL) of young patients with Achondroplasia and only a few HrQoL instruments exist for this patient group. To better understand the consequences and impact of this condition on the life of the affected children and adolescents, the objective of this study was to develop a condition-specific patient-reported outcome measure to assess HrQoL, wellbeing and functioning, considering the patients’ and their parents’ perspective. Method: In a first step, focus group data of a previous study with individuals with Achondroplasia was qualitatively analyzed. To identify relevant concepts associated with HrQoL, wellbeing and functioning, statements in the focus group discussions were coded regarding the International Classification of Functioning – Children and Youth (ICF-CY) and used for item generation. In a second step pilot testing and new focus group discussions with a cognitive debriefing were conducted with children and adolescents with Achondroplasia and their parents. Qualitative and quantitative data was used to finally select items for the subsequent field test. Results: In total, 59 items were generated based on codes of the ICF-CY and included in a pilot test with a cognitive debriefing. Following the results of the pilot test, the field test version includes seven scales with 35 Likert-scaled items assigned to the main ICF-CY components: Body functions (global and specific mental functions), body structures (structures related to movement), activities and participation (community, social and civic life/ interpersonal interactions & relationships/ mobility/ self-care/ domestic life) and environmental factors (attitudes/ support & relationships). The questionnaire is available in self- and parent report in the age groups 8-11 and 12-14 years and for parent-report in the age group 5-7 years. Conclusion: The APLES questionnaire is based on the international language of the ICFCY and addresses in sufficient detail the special situation, specific burdens, restrictions and resources of children and adolescents with Achondroplasia, especially with regard to body structures. Applying the APLES questionnaire in research or in medical practice can help to better understand HrQoL, wellbeing and functioning in this patient group. Subsequently, a field and retest is needed to psychometrically test the new instrument.
Keywords: ICF-CY; Achondroplasia; HrQoL; patient-reported outcomes